ANALISIS PEMBIASAAN PAGI MENYANYIKAN LAGU NASIONAL DALAM MEMBANGUN KARAKTER CINTA TANAH AIR PADA SISWA KELAS IV D DI SDN WONOTINGAL - Devy Nur Saputri; Harto Nuroso; Noor Miyono; Bernardus Irianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Morning habits are routine habits carried out in an educational environment where students are regularly and continuously taught a behavior or behavior that they tend to emphasize in certain situations without taking their own initiative to show it to other people or society. In dealing with certain scenarios or circumstances, one of the examples given relates to how students' characters are formed. The aim of this research is to find out how the habit of singing national songs in the morning builds the character of love for the country in class IV D students at SDN Wonotingal. The collection methods used are observation, interviews and documentation. The results of this research show that the morning habit of singing the national song for class IV D students at SDN Wono continues to run well every day. The morning habitual activity of singing the national song succeeded in building the character of love for the country in students, which was reflected in their daily attitudes and behavior.